2021
DOI: 10.1111/grow.12527
|View full text |Cite
|
Sign up to set email alerts
|

Cultural barriers, institutional distance, and spatial spillovers: Evidence from regional industrial evolution in China

Abstract: This study empirically explores the formation of interregional cultural barriers that affect spatial spillovers within the framework of institutional distance based on evidence of regional industrial evolution in China. With dialect as the proxy of culture, this study finds that, first, regional cultural differences will hinder the spatial spillovers of industrial evolution, but the formation of cultural barriers is not only related to culture itself but also closely related to the formal institutional distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The level of socio-economic development is clustered across regions in China. That is, the overall similarity in economic, educational, cultural, and industrial structure of neighboring provinces is higher than that of provinces farther away from each other [27,28,29]. If the level of the gender pay gap is influenced by the level of socio-economic development, G (2) is expected to be very small, which means the level of the gender pay gap in neighboring provinces is similar.…”
Section: Resultsmentioning
confidence: 99%
“…The level of socio-economic development is clustered across regions in China. That is, the overall similarity in economic, educational, cultural, and industrial structure of neighboring provinces is higher than that of provinces farther away from each other [27,28,29]. If the level of the gender pay gap is influenced by the level of socio-economic development, G (2) is expected to be very small, which means the level of the gender pay gap in neighboring provinces is similar.…”
Section: Resultsmentioning
confidence: 99%
“…MI was developed by the National Economic Research Institute (NERI), an influential think tank in China, and the first MI report was published in 2000. Following Mao and Mao (2021), we calculate the intercity institutional friction (or institutional distance) using the following equation:…”
Section: Marketization Index As a Measure Of Institution Proximitymentioning
confidence: 99%
“…In the same vein, some authors argue that the rapid development of the Chinese economy is the result of collective learning between industries and regions (neighboring regions) [37]. In addition to geographical distance, cultural differences and institutional distance have a significant impact on the evolution of China's regional comparative advantage by affecting the location of knowledge flow [6]. However, less attention has been paid to the impact of multilocational knowledge learning (including proximity and distance learning) on the evolution of China's regional comparative advantage.…”
Section: Methodsmentioning
confidence: 99%
“…Following earlier work [2], recent studies have focused on the impact of neighboring regions on the evolution of local industries [3][4][5]. Some empirical studies found that when knowledge is disseminated to adjacent regions, it can trigger the evolution of the comparative advantage there [6]. According to Bahar, Hausmann and Hidalgo [3] and Boschma, Martín and Minondo [4], new knowledge of neighboring countries has an important impact on the development of local industries.…”
Section: Introductionmentioning
confidence: 99%